2017
DOI: 10.1007/s40123-017-0102-x
|View full text |Cite
|
Sign up to set email alerts
|

Twice-Daily vs. Once-Daily Dosing with 0.075% Bromfenac in DuraSite: Outcomes from a 14-Day Phase 2 Study

Abstract: IntroductionBromfenac is a well-known topical ophthalmic nonsteroidal anti-inflammatory drug (NSAID) that is commercialized in the USA and other regions of the world. A new formulation, 0.075% bromfenac in DuraSite®, was developed to treat postoperative inflammation and reduce pain in patients who have undergone cataract surgery. We hypothesized that efficacy and safety would be enhanced with twice-daily (BID) dosing compared to once-daily (QD) dosing.MethodsThis was a multicenter, double-masked, comparative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Our findings largely corroborated with previous studies evaluating the clinical efficacy of topical NSAIDs. 13,16,25 The AC flare measured by flaremeter was significantly higher in the control group than the patients who received bromfenac over 3 months of follow-up, with both once-daily and twice-daily bromfenac groups having comparable outcomes. Endo et al reported a decrease in AC flare to the preoperative level by 2 weeks in the bromfenac group but persistently elevated levels through 6 weeks in the steroid group.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings largely corroborated with previous studies evaluating the clinical efficacy of topical NSAIDs. 13,16,25 The AC flare measured by flaremeter was significantly higher in the control group than the patients who received bromfenac over 3 months of follow-up, with both once-daily and twice-daily bromfenac groups having comparable outcomes. Endo et al reported a decrease in AC flare to the preoperative level by 2 weeks in the bromfenac group but persistently elevated levels through 6 weeks in the steroid group.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, PLGA (Casey et al, 2019;Ganugula et al, 2020;Luo et al, 2020), PLA (Sakai et al, 2006;Sakai et al, 2011), poly-caprolactone (PCL) (Yenice et al, 2008;du Toit et al, 2013), polyacrylic acid (PAA) (Trattler and Hosseini, 2017), and poly (amidoamine) (PAMAM) (Iezzi et al, 2012;Yavuz et al, 2016) are the most commonly used synthetic biomaterials as carriers of anti-inflammatory medications in ophthalmic therapy. According to Casey et al (2019), PLGA and PLA particles have broad-acting mechanisms that inhibit TLR signaling by programming innate immune cells, and they exhibit inherent immunomodulatory properties depending on their physiochemical properties.…”
Section: Ocular Disease Anti-inflammatory Agentmentioning
confidence: 99%
“…The most common immunosuppressive agents are steroids. They have been used in a large number of commercial antiinflammatory ocular drugs such as Bromfenac and INVELTYS ™ , both of which contain cross-linked PAA or chitosan polymer; they are widely used for treating post-ocular surgery inflammation, reducing post-surgery pain, and DED (Bowman et al, 2009;Schopf et al, 2015;Trattler and Hosseini, 2017;Kim et al, 2018;Gupta and Venkateswaran, 2021). Steroidal immunosuppressants have several drawbacks; they require high administration dosages, frequent injections in chronic ocular inflammatory diseases that lead to defects in the innate immune system, and other long-term side effects such as cataracts and IOP in the eye.…”
Section: Steroidsmentioning
confidence: 99%